Arterial Spin Labeling MRI for Predicting Microvascular Invasion of T1 Staging Renal Clear Cell Carcinoma Preoperatively - Zhang, Han-Mei; Wen, Da-Guang; Wang, Yi; Bao, Yi-Ge; Yuan, Yuan; Chen, Yun-Tian; Song, Bin (Frontiers in Oncology, 2021)
Background: Microvascular invasion (MVI) is a valuable factor for T1 staging renal clear cell carcinoma (ccRCC) operation strategy decision, which is confirmed histopathologically post-operation. This study aimed to prospectively evaluate the performance of arterial spin labelling (ASL) MRI for predicting MVI of T1 staging ccRCC preoperatively. Methods: 16 volunteers and 39 consecutive patients were enrolled. MRI examinations consisted of ASL (three post label delays separately) of the kidney, followed by T1 and T2-weighted imaging. Two sessions of ASL were used to evaluate the reproducibility on volunteers. Renal blood flow of renal cortex, medulla, the entire and solid part of tumor were measured on ASL images. Conventional imaging features were extracted. MVI and WHO/ISUP classification were evaluated histopathologically. A paired t‐test was used to compare the renal cortical and medullary between ASL 1 and ASL 2. The reproducibility was assessed using the intraclass correlation. Differences in mean perfusion between the entire and the solid part of tumors with or without MVI were assessed separately using Student’s t test. The diagnostic performance was assessed. Logistic regression analysis was used to indicate the independent prediction index for MVI. Results: The two sessions ASL showed no significant difference between the mean cortex values of RBF. The cortical RBF measurements demonstrated good agreement. 12 ccRCCs presented with MVI histopathologically. Mean perfusion of the solid part of tumors with MVI were 536.4±154.8 ml/min/100 g (PLD1), 2912.5±939.3 ml/min/100 g (PLD2), 3280.3±901.2 ml/min/100 g (PLD3). Mean perfusion of the solid part of tumors without MVI were 453.5±87.2 ml/min/100 g (PLD1), 1043.6±695.8 ml/min/100 g (PLD2), 1577.6±1085.8 ml/min/100 g (PLD3). These two groups have significant difference at all the PLDs (p<0.05). The RBF of PLD1 of the solid part of tumor perfusion showed well diagnostic performance for predicting MVI: sensitivity 75%, specificity 100%, positive predictive value 66.7%, and negative predictive value 95.7%. The maximum diameter of the tumor, ill-defined margin and the solid part of tumor perfusion were the independent prediction index for MVI. Conclusion: ASL MR imaging has well reproducibility for renal cortex, and good diagnostic performance for predicting MVI for ccRCC.